Microcontroller Based Boost PID - Mohd Rubaee, Munajah (2008)
Electronic devices are used to convert electrical power from one form to another are called power electronic. It is function by using semiconductor as power switches to controlling or modifying a voltage and current. Everyday electronic appliance and high power conversion equipment is the examples of power electronic applications. But usually power electronic are applied in conversion of ac to dc, conversion of unregulated dc voltage to regulated dc voltage and conversion of power source from one amplitude and frequency to another amplitude and frequency. There are many disciplines from electrical engineering involve in designing power conversion equipment, it includes application of circuit theory, control theory, electronic, electromagnetic, microprocessor and heat transient. Power electronic is a fast-growth area in electrical engineering due to advances in semiconductor switching capability combine with the desired to improve the efficiency and performance of electrical devices. An electronic switch is characterized by having two states ‘on’ and ‘off’, ideally being either a short circuit or an open circuit. Application using switch are desirable because of the relatively small power loss in the devices. If the switch is ideal either the switch voltage or the switch current is zero, making the power absorbed by it zero. Real devices absorb some power when in the on state and when making transitions between on and off, but circuit efficiencies can still be quite high. Electronic devices such as transistors can also operate in the linear range where both voltage and current are nonzero, but it is desirable to use these devices as switches when processing power. Dc – dc converter are power electronic that convert dc voltage to a different voltage level. This circuit is classified as switch mode dc-dc converter, also called as switching power supplies switchers. Boost converter is one of the types, the circuit function to convert a dc-dc voltage where it will produce a higher output voltage. Therefore I choose microcontroller based boost PID as my final year project, where instead using function generator as the pulse supply, I implemented PIC microcontroller as pulse supply and in order to maintain the output, proportional controller is program as an error correction at the output terminal via the feedback loop.